Skin Temperature of Slaughter Pigs With Tail Lesions - Teixeira, Dayane Lemos; Boyle, Laura Ann; Enríquez-Hidalgo, Daniel (Frontiers in Veterinary Science, 2020)
The aim of this study was to assess the effect of tail lesion severity on skin temperature of slaughter pigs measured at the base of the tail and the ear by infrared thermography camera and to evaluate the association between the temperature measurements. Pigs were randomly selected in the lairage, containing approximately 200-pigs/ pen lairage. Tail lesions were scored according to severity, using a 0-4 scale. Tail lesion scores 0 and 1 were summed as it was difficult to distinguish healed lesions from mild lesions due to animal dirtiness. In total, 269 study pigs were imaged at the two locations. The effect of tail lesion score and sex of the pig on the highest temperature of the infrared image areas were analysed using linear mixed models. Association between the tail base and ear base temperatures was evaluated using Pearson correlation. Skin temperature measured at the base of the tail was significantly lower for tails scored 0-1 than for all other tail lesion scores (P<0.05). Pigs with tail lesion scored 2 had significantly lower skin temperatures at the base of the tail than pigs with tail lesion scored 3 or 4 (P<0.05) while there was no difference in skin temperature at the base of the tail between pigs with tail lesion scored 3 and 4 (P>0.05). Skin temperature measured at the ear base was significantly lower for pigs with tail lesion scored 0-1 than pigs of all other tail lesion scores (P<0.05) with no difference between the other scores (P>0.05). Furthermore, there was an association between the two measurements (r = 0.50; P < 0.001). The findings suggest that even pigs with moderate tail lesions (score 2) may have general inflammation and infection, evidenced by the elevated systemic temperature compared to pigs with none or mild tail lesion (score 0-1).